The Bridge of death - Atwood, Megan (Minneapolis Darby Greek, 2012)
Best friends Jinx and Jackson suspect a ghost may be responsible when several popular students decide to harm themselves by jumbing off a local bridge
3
Keywords: Supernatura -- l Fiction; horror -- novels